CEMES 2017: Ostře sledovaná analýza [CEMES 2017: closely watched analysis] - Křeček, Jan (Mediální studia [Media Studies], 2018)
In the end of the year 2017 and at the begging of the following has been very intensively discussed the pre-election analyse of broadcasting of the Český rozhlas and Česká televize. This essay is focused not only on the named above analyse but on the critics of this analyse also.
https://katalog.adlr.link/Record/ai-53-736019